(untitled) (World Science, 2018)
The purpose of the study was evaluating the peculiarity of bone mineral density (BMD) and body composition in patients with spinal cord injury (SCI). 51 men with SCI were enrolled to the study. The comparison group consists of 51 healthy men which were standardized by age and body weight. The study revealed in patients with SCI significantly higher rate of osteoporosis (84.31%) and sarcopenia (43.14%) in comparison with healthy men (1.96% and 25.49% accordingly). In healthy men the correlation analysis revealed the wide-ranging influence of body composition on lower extremities BMD. Thus, femur neck BMD is determined by the lean mass of upper extremities (r = 0.33, p <0.05), lower extremities (r = 0.38, p <0.05), trunk (r = 0.41, p <0.05) and total body (r = 0.43, p <0.05). Hip BMD depends on the lean mass of trunk (r = 0.36, p <0.05) and total body (r = 0.34, p <0.05). Lower extremities BMD correlates with lean mass of trunk (r = 0.33, p <0.05) and lower extremities (r = 0.32, p <0.05). In men with SCI it was found the correlation between femur neck BMD and trunk lean mass (r=0.30, p<0.05); hip BMD correlates with lean mass of trunk (r=0.31, p<0.05) and lower extremities (r=0.35, p<0.05); lower extremities BMD correlates with lean mass of trunk (r = 0.41, p <0.05) and lower extremities (r = 0.32, p <0.05). Consequently, our study showed the influence of lean body mass on lower extremities BMD in both groups, which should be taken into account during managements of patients with SCI.